Tourists' impulse buying behavior at duty-free shops: the moderating effects of time pressure and shopping involvement. Issue 3 (24th March 2017) - Sohn, Hae-Kyung; Lee, Timothy J.
ABSTRACT: This study investigates the consumer behavior of tourists at duty-free shops who experience different limitations on shopping than do consumers at general shopping malls. The target for sampling was outbound tourists who shopped in two hotel duty-free shops in Seoul, Korea. The final analysis used data from 343 respondents and the results revealed (1) the more positive the emotions felt by tourists, the more impulsive buying behavior occurs; (2) time pressure during shopping reinforces negative emotions, resulting in increased affective impulse buying; and (3) increased shopping involvement directly increases cognitive impulse buying.